Biology and Behaviour of a Parasitoid, Parasierola Sp. (Hymenoptera : Bethylidae on Trachylepidia fructicassiella Ragnot. A Seed Borer of Cassia roxburghii - Ahmad, Mukhtar; Salarkhan, A. M. (Indian Forester, 1986)
Parasierola sp.is the bethylid paralnold on the larvae of Trachylepidia fructicassiella. Mating of the two sexes Observed Z to 3 times a day. Maximum number of emergences of adults were observed from the eggs deposited during first week and raduced considerably from the eggs laid during successive days. Total developmental period varied from 5.86 Â± 7.44 to 14.8 Â± 1.13 days. Pupal period was larger than the period required for Incubation + larval development. The developmental period of the offsprings from first to sixth sucessive avipositions varied significantly and found shortened for the offsprings from the older females. Females live longer than the males. The age of the females was also found to be related with the production of sexes as the percentage of females was higher at the older age. Parasierola sp. Was found to be prevalent only during July to September with the abundance of the host larvae.